The new Turkey and its discontents - Waldman, Simon A. 2015- (Oxford University Press, 2017)
The Turkey of today little resembles that of recent decades. Its economy has expanded hugely, new political elites have emerged, and the once powerful Kemalist military is no longer a potent and dominant political player. Meanwhile, new prosperity has had many unexpected social and political repercussions, pre-eminent among which is the advent of the Justice and Development Party (AKP), which first came to power in 2002 by downplaying its Islamist leanings and marketing itself as a centre-right party. After several terms in office, and amid unprecedented popularity, the conduct of the AKP and its leading cadres has faced growing criticism. Turkey has yet to solve its Kurdish question, and its foreign policy is increasingly under threat as it balances relations with Iran, Israel, Iraq and Russia, to name only a few of its more demanding interlocutors. Widespread domestic protests gripped the country in 2013. The government is now perceived by many to be corrupt, unaccountable, intimidating of the press and intolerant of alternative political views and criticism.0Has this once promising democracy descended into a tyranny of the majority led by a charismatic leader, Recep Tayyip Erdogan? Is Turkey more polarised now than ever in its recent history? These are among the questions posed in this timely primer on a rising economic power